The effect of an augmented reality teaching kit on visualization, cognitive load and teaching styles - Ismail, Mohd Erfy; Utami, Pipit; Ismail, Irwan Mahazir; Khairudin, Moh.; Amiruddin, Mohd Hasril; Lastariwati, Badraningsih; Maneetien, Nopadon (Kemenristekdikt, 2018)
The purpose of this study was to identify the visualization of the students, the students' cognitive load, and the teaching style of the teacher while teaching using the augmented reality (AR) teaching kit in the classroom. The population involved 90 Welding Technology students at Vocational College of Batu Pahat. The purposive sampling method was used and involved 30 respondents. The instrument used was a questionnaire to obtain information. Data were collected and analyzed descriptively. Based on the pilot study, the Cronbach Alpha value was 0.94. The results showed that the use of an AR teaching kit was able to enhance students’ visualization and reduced the cognitive load experienced by the students. In addition, teaching and learning are more interesting because of the teaching style of teachers who use theories and practices simultaneously. Furthermore, the use of AR in education can enhance the visualization of students abstractly, which helps them when conducting experiential tests and establishing a safe teaching and learning environment.